The Auxin Signaling Repressor IAA8 Promotes Seed Germination Through Down-Regulation of ABI3 Transcription in Arabidopsis - Hussain, Shah; Kim, Sun Ho; Bahk, Sunghwa; Ali, Akhtar; Nguyen, Xuan Canh; Yun, Dae-Jin; Chung, Woo Sik (Frontiers in Plant Science, 2020)
Seed germination is a complex biological process controlled by various regulators, including phytohormones. Among these, abscisic acid and gibberellic acid inhibit and promote seed germination, respectively. Many studies have addressed the biological roles of auxin in plant growth and development, but very few have considered its role in seed germination. Here, we identified a novel function of the auxin signaling repressor Aux/IAA8 during seed germination. The IAA8 loss-of-function mutant iaa8-1 exhibited delayed seed germination. The phenotype of iaa8-1 was restored by ectopic expression of IAA8. Interestingly, IAA8 accumulated to high levels during seed germination, which was achieved not only by increased protein synthesis but also by the stabilization of IAA8 protein. We also showed that IAA8 down-regulates the transcription of ABSCISIC ACID INSENSITIVE3 (ABI3), a negative regulator of seed germination. Our study, thus strongly suggest that the auxin signaling repressor IAA8 acts as a positive regulator of seed germination in Arabidopsis thaliana.